ANALISIS BIBLIOMETRIK ATAS PENELITIAN BELANJA PERPAJAKAN MENGGUNAKAN APLIKKASI VOSVIEWER - Diperhatikan Halawa; Fitriana Fitriana; Rachmat Agus Santoso (ITB AAS INDONESIA, 2024)
Tax spending leads to reduced tax revenue from certain taxpayers. It has been a lot to do the study of this field. The purpose of this study is to analyze the classification of tax expenditure research articles, identify topic trends in tax expenditure research, and analyze opportunities for tax spending research topics in the future. The research method used a five-step method of bibliometric analysis and data analysis was used vosviewer application. Article searches were used through data from Scopus with the keyword